2020
DOI: 10.48550/arxiv.2003.04783
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probing the inflationary background of gravitational waves from large to small scales

William Giarè,
Alessandro Melchiorri

Abstract: The detection of Primordial Gravitational Waves (PGWs) is one of the most important goals of modern cosmology since PGWs can both provide substantial evidence for primordial inflation and shed light on its physical nature. Small scale experiments on gravitational waves such as Ligo-Virgo and, in future, LISA and Einstein Telescope (ET), are sensitive to the stochastic background, ΩGW. So they can be used to constrain the inflationary parameters. In performing this kind of analysis, as recently done also by the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…At higher frequencies, the expected signal can be extrapolated, assuming the power-law is valid across many decades in scale. However, the assumption of a power-law across a large frequency range was shown to introduce sizeable errors on the scales probed by interferometers [8]. In this work we did not assume a powerlaw, instead directly reconstructing the tensor power spectrum in logarithmic frequency bins using the latest data from Planck and BICEP2/Keck.…”
Section: Introductionmentioning
confidence: 99%
“…At higher frequencies, the expected signal can be extrapolated, assuming the power-law is valid across many decades in scale. However, the assumption of a power-law across a large frequency range was shown to introduce sizeable errors on the scales probed by interferometers [8]. In this work we did not assume a powerlaw, instead directly reconstructing the tensor power spectrum in logarithmic frequency bins using the latest data from Planck and BICEP2/Keck.…”
Section: Introductionmentioning
confidence: 99%
“…In this work we further investigate higher-curvature corrections at leading order in the breaking of de Sitter isometries. We show that, along with the above mentioned violation of the consistency relation, other non trivial signatures can be left in the tensor two-point function and in particular the running of the tensor tilt can be some order of magnitude larger than expected in the standard slow roll hierarchy [21,66,67], possibly affecting the small scale behavior of tensor perturbations [68][69][70][71][72]. If a violation of the slow roll consistency relation will be observed, a combined analysis of the tilt and the running could in principle shed light on its higher-curvature nature.…”
Section: Introductionmentioning
confidence: 77%
“…Indeed, even a small positive spectral index could produce an enhanced signal on small scales, given that the predicted power-spectra span ∼ 25 orders of magnitude in the frequency domain [7,62]. In recent works [63,64] it has been shown that in order to be detectable with the Laser Interferometer Space Antenna (LISA) and the Einstein Telescope the spectrum for inflationary gravitational waves must be considerably enhanced at scales smaller than the CMB ones. In particular, this requires a blue spectrum with n t 0.1 − 0.2, which is almost one order of magnitude greater than the typical values that we are finding.…”
Section: Eft Inflation Withmentioning
confidence: 99%